Estimasi Parameter Sel Fotovoltaik Menggunakan Algoritma Optimasi Moth-Flame - Fitriah Husin; Ayong Hiendro (Postgraduate, University of Mataram, 2025)
Estimation of photovoltaic cell parameters from experimental data is an important part of photovoltaic system performance modeling and optimization. This study aims to estimate the parameters of photovoltaic cells. The photovoltaic models used are the one-diode model (ODM) and the two-diode model (TDM). Optimization is performed using the moth-flame optimization (MFO) algorithm. The root mean square error (RMSE) method is applied to determine the accuracy of the estimated parameters. Experimental results show that the MFO algorithm is able to obtain photovoltaic cell parameters with a high level of accuracy, both in ODM and TDM. The current-voltage (I-V) and power-voltage (P-V) curves between the measured and estimated data also show a very good match. In addition, the optimization algorithm outperforms most metaheuristic algorithms applied in photovoltaic cell parameter determination. Thus, the MFO algorithm is suitable to be applied in determining the photovoltaic cell parameters.